The prevalence of depressive symptoms in high-performance athletes: a systematic review - Golding, L.; Gillingham, R. G.; Perera, N. K. P. (The Physician and Sportsmedicine, 2020)
Objective: To provide an up-to-date overview of the prevalence of depressive symptoms in high-performance athletes and describe the tools used to assess for these in order to identify knowledge gaps and potential future research priorities.